Less is more: extreme genome complexity reduction with ddRAD using Ion Torrent semiconductor technology. (10th March 2015) - Pukk, Lilian; Ahmad, Freed; Hasan, Shihab; Kisand, Veljo; Gross, Riho; Vasemägi, Anti
Abstract Massively parallel sequencing a small proportion of the whole genome at high coverage enables answering a wide range of questions from molecular evolution and evolutionary biology to animal and plant breeding and forensics. In this study, we describe the development of restriction‐site associated DNA (RAD) sequencing approach for Ion Torrent PGM platform. Our protocol results in extreme genome complexity reduction using two rare‐cutting restriction enzymes and strict size selection of the library allowing sequencing of a relatively small number of genomic fragments with high sequencing depth. We applied this approach to a common freshwater fish species, the Eurasian perch (Perca fluviatilis L.), and generated over 2.2 MB of novel sequence data consisting of ~17 000 contigs, identified 1259 single nucleotide polymorphisms (SNPs). We also estimated genetic differentiation between the DNA pools from freshwater (Lake Peipus) and brackish water (the Baltic Sea) populations and identified SNPs with the strongest signal of differentiation that could be used for robust individual assignment in the future. This work represents an important step towards developing genomic resources and genetic tools for the Eurasian perch. We expect that our ddRAD sequencing protocol for semiconductor sequencing technology will be useful alternative for currently available RAD protocols.